2020
DOI: 10.1002/ccd.29427
|View full text |Cite
|
Sign up to set email alerts
|

Fractional flow reserve guided versus angiographic guided surgical revascularization: A meta‐analysis

Abstract: Background Clinical benefits of FFR (Fraction Flow Reserve) driven CABG (Coronary Artery Bypass Graft) remain to be established. Methods All randomized controlled trials (RCTs) and observational studies with multivariable adjustement were included. MACE (Major Adverse Cardiac Events) was the primary end point, while its single components (death, myocardial infarction, and total vessel revascularization [TVR]) along with number of anastomoses, on pump procedures and graft occlusion at angiographic follow‐up wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…
To the Editor, We read with interest the meta-analysis by Bruno et al in the journal Catheterization and Cardiovascular Interventions on the topic of use of fractional flow rate (FFR) compared with angiography alone for coronary artery bypass graft (CABG) surgery decision-making. 1 This study shares similarities with the recent meta-analysis we performed on this subject. 2 Both studies showed overall similar outcomes for FFR based versus angiography-based CABG.
…”
supporting
confidence: 81%
“…
To the Editor, We read with interest the meta-analysis by Bruno et al in the journal Catheterization and Cardiovascular Interventions on the topic of use of fractional flow rate (FFR) compared with angiography alone for coronary artery bypass graft (CABG) surgery decision-making. 1 This study shares similarities with the recent meta-analysis we performed on this subject. 2 Both studies showed overall similar outcomes for FFR based versus angiography-based CABG.
…”
supporting
confidence: 81%
“…To the Editor, We thank the authors for their comment on our meta-analysis about fractional flow reserve (FFR) versus angiographic-guided coronary bypass graft (CABG). 1,2 The authors reported outcomes comparable with our findings, confirming that FFR-driven revascularizations entail a reduction in the number of anastomoses and the need for on-pump surgical procedures as compared with angiographic-driven ones, with a neutral impact on adverse events, including death, myocardial infarction, and target vessel revascularization at a mid-term follow-up ranging from 6 to 85 months. 2,3 Moreover, arterial conduits were more likely to be used in the FFR group.…”
supporting
confidence: 86%
“…The FFR-guided patients received a lower number of anastomoses, more arterial grafts and more frequently underwent off-pump procedures, which are associated with a reduction of (short-term) complications. [59][60][61][62] Moreover, a significant improvement in graft patency compared to ICA-guided CABG is observed. 59 A possible explanation for the apparent lack of benefits for FFR-guided CABG can be found in a process called surgical collateralizationgrafting might protect against the effects of progression of coronary lesions in proximal segments.…”
Section: Cabgmentioning
confidence: 95%
“… 59 A possible explanation for the apparent lack of benefits for FFR-guided CABG can be found in a process called surgical collateralization – grafting might protect against the effects of progression of coronary lesions in proximal segments. 1 , 61 Grafting of non-critically diseased coronary arteries is associated with a higher rate of graft closure due to competitive flow in the grafted coronary artery. 1 , 21 Functional testing may help guide the surgical revascularization strategy in ambiguous lesions.…”
Section: Practical Aspects and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation